Mu2e Crystal Calorimeter Readout Electronics: Design and Characterisation - Nikolay Atanov; Vladimir Baranov; Leo Borrel; Caterina Bloise; Julian Budagov; Sergio Ceravolo; Franco Cervelli; Francesco Colao; Marco Cordelli; Giovanni Corradi; Yuri Davydov; Stefano Di Falco; et al. (Instruments, 2022)
The Mu2e experiment at Fermi National Accelerator Laboratory will search for the charged-lepton flavour-violating neutrinoless conversion of negative muons into electrons in the Coulomb field of an Al nucleus. The conversion electron with a monoenergetic 104.967 MeV signature will be identified by a complementary measurement carried out by a high-resolution tracker and an electromagnetic calorimeter, improving by four orders of magnitude the current single-event sensitivity. The calorimeter—composed of 1348 pure CsI crystals arranged in two annular disks—has a high granularity, 10% energy resolution and 500 ps timing resolution for 100 MeV electrons. The readout, based on large-area UV-extended SiPMs, features a fully custom readout chain, from the analogue front-end electronics to the digitisation boards. The readout electronics design was validated for operation in vacuum and under magnetic fields. An extensive radiation hardness certification campaign certified the FEE design for doses up to 100 krad and 10<semantics>12</semantics> n<semantics>1MeVeq</semantics>/cm<semantics>2</semantics> and for single-event effects. A final vertical slice test on the final readout chain was carried out with cosmic rays on a large-scale calorimeter prototype.